Exploring the impact of cooking techniques and storage conditions on resistant starch levels in mung beans and its effect upon blood glucose level and lipid profile in vivo - Chauhan, Saloni; Kaur, Harpreet; Aggarwal, Renuka; Kaur, Prabhjot; Bains, Kiran (Frontiers in Nutrition, 2024)
This study aimed to assess the effects of cooking and storage temperature on the formation of resistant starch in processed mung bean, as well as its effect on blood glucose levels and lipid profile in humans and rats. The common cooking methods namely boiling, steaming after germination, roasting and pressure cooking were chosen. The cooked samples were stored at different temperatures including freshly prepared within 1h (T1), stored for 24 h at room temperature (20-22⁰C) (T2), kept at 4⁰C for 24 h (T3) and reheated after storing at 4⁰C for 24 h (T4). The study revealed that germinated-steamed mung beans had significantly higher levels of resistant starch (27.63±0.76), and lower level of glycemic index (26.28±3.08) and amylose (40.91±0.06) when stored at 4⁰Cfor 24h (T3) followed by (T2), (T4) and (T1) as compared to other cooking methods (boiling, pressure cooking and roasting). The germinated-steamed mung beans (T1) resulted in 96% decline in blood glucose parameters of rats (thirty-six Wistar albino rats aged two to three months were selected) than the control group as observed in 28 days diet intervention (100mg/kg resistant starch orally). There is a need to make people aware about the selection of appropriate cooking (steamed after germination) and storage methods (T3) to increase the RS content and to lower the glycemic index of food at domestic level.